Association between depression and oxidative balance score: National Health and Nutrition Examination Survey (NHANES) 2005–2018 - Liu, Xuna; Liu, Xuyan; Wang, Yiwen; Zeng, Beibei; Zhu, Boxu; Dai, Fei (Journal of affective disorders, 2023)
Few studies have investigated the relationship between systemic oxidative stress status and depression. The oxidative balance score (OBS) was used to assess systemic oxidative stress status, with higher OBS scores implying exposure to more antioxidants. This study aimed to explore whether OBS is associated with depression. 18,761 subjects from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 were selected. Depression was diagnosed by the Patient Health Questionnaire (PHQ-9, score ≥ 10). OBS was scored by 20 dietary and lifestyle factors. Weighted logistic regression and restricted cubic splines (RCS) were used to assess the association between OBS and depression. The prevalence of depression was 8.42 %. There was a significant negative nonlinear relationship between OBS, dietary OBS, lifestyle OBS and depression (p for nonlinear < 0.05). Compared to the lowest quartile of OBS, the adjusted ORs for the highest quartile of OBS, dietary OBS, and lifestyle OBS and depression were 0.290 (95 % CI: 0.193–0.434), 0.500(95 % CI: 0.380–0.658), 0.403(95 % CI: 0.299–0.545) respectively, and all P for trend < 0.001. In stratified analyses, three OBS were negatively associated with the odds of depression across sex groups (all P for trend < 0.05), and the OR was smaller in the female group than in the male group. Cross-sectional data and absence of drug considerations. OBS was strongly negatively associated with depression, especially in females. The findings underline the significance of adhering to an antioxidant diet and lifestyle, which helps prevent depression and appears to be of greater benefit to women. •Oxidative balance score (OBS) was used to assess systemic oxidative stress status.•Higher OBS scores mean greater exposure to antioxidants.•OBS was strongly negatively associated with depression, especially in females.•Adhering to an antioxidant diet and lifestyle can prevent depression.